Germination biology of four climatically varied populations of the invasive species African lovegrass (Eragrostis curvula). Issue 2 (12th March 2021) - Roberts, Jason; Florentine, Singarayer; van Etten, Eddie; Turville, Christopher
Abstract: African lovegrass [ Eragrostis curvula (Schrad.) Nees] is a highly invasive C4 perennial grass that threatens global biodiversity. Appropriate management of this species has been hampered by a lack of knowledge concerning its seed ecology, resulting in significant economic and environmental impacts within various environments. Consequently, this study explored the effects of a selection of environmental factors (photoperiod, alternating temperature, pH, and salinity) by analyzing several measures of germination on four geographically distinct populations of E. curvula to assist in its extirpation from infested sites. Seeds were collected in Australia from Maffra and Shepparton, VIC; Tenterfield, NSW; and Midvale, WA. Key results showed that seeds from Maffra (54% vs. 79%), Tenterfield (38% vs. 61%), and Shepparton (34% vs. 71%) had significantly reduced germination in complete darkness compared with an alternating 12-h light and 12-h dark photoperiod, whereas Midvale had consistent germination (91% vs. 99%). Temperatures between 17/7 C reduced germination for Maffra (42% vs. 73%), Tenterfield (34% vs. 55%), and Shepparton (33% vs. 59%) compared with the mean of all other temperature combinations, whereas Midvale had consistent germination. Furthermore, germination for all populations was consistent between pH 4 and 9. For salinity, germination was significantly reduced at ≥100 mM for Maffra (29% vs. 67%), ≥150 mM for Tenterfield (29% vs. 94%) and Shepparton (39.5% vs. 81.5%), and 250 mM for Midvale (39% vs. 82%) compared with the mean of all other concentrations. Although each trial was conducted independently, the data can be used to generate species-targeted management. Such strategies include maintaining high levels of quarantine and hygiene programs to avoid future spread; where practical, applying light-limiting strategies (mulching, tilling, or scraping) for the Maffra, Tenterfield, and Shepparton populations; and maintaining management efforts year-round, as the species can germinate under a wide range of conditions.